Biomechanical Comparison of the Long Head of the Biceps Tendon Versus Conjoint Tendon Transfer in a Bone Loss Shoulder Instability Model. Issue 11 (22nd November 2019) - Bokshan, Steven L.; Gil, Joseph A.; DeFroda, Steven F.; Badida, Rohit; Crisco, Joseph J.; Owens, Brett D.
Background: Augmentation of Bankart repair with long head of the biceps tendon transfer has been previously described, although there is a paucity of literature describing its biomechanical effects. Purpose/Hypothesis: The purpose of this study was to assess the effect of augmenting Bankart repair with either the conjoint tendon or the long head of the biceps tendon, both with and without subcritical (13%) glenoid bone loss. We hypothesized that, in a cadaveric model, augmenting Bankart repair with the long head of the biceps tendon would restore a greater degree of stability compared with augmenting Bankart repair with the conjoint tendon. Study Design: Controlled laboratory study. Methods: A total of 12 cadaveric shoulders were tested on a 6-degrees-of-freedom robotic musculoskeletal simulator to measure the peak resistance force due to an anterior displacement of 1 cm. The rotator cuff muscles were loaded during testing to simulate physiological conditions. The following test conditions were used for each specimen: (1) intact shoulder, (2) Bankart lesion with 13% anterior bone loss, (3) 13% bone loss with Bankart repair (anchors placed at the 3-, 4-, and 5-o'clock positions), (4) 13% bone loss with both Bankart repair and transfer of the long head of the biceps tendon, and (5) 13% bone loss with Bankart repair and transfer of the conjoint tendon. Results: Labral repair with the addition of long head of the biceps tendon transfer had the greatest peak resistance force to anterior displacement among all groups (54.1 ± 5.5 N) and was significantly stronger than both standard Bankart repair by 16.3% (46.5 ± 7.6 N; P = .039) and the conjoint transfer procedure by 16.6% (46.4 ± 7.7 N; P = .008). Conclusion: Given the susceptibility of recurrent instability in shoulders with subcritical bone loss after isolated labral repair, it is important to consider augmenting Bankart repair in high-risk patients to avoid potential recurrence and the need for reoperations. Transferring the long head of the biceps tendon to the anterior glenoid represents one possible augmentation. Clinical Relevance: We present biomechanical data for a relatively novel technique for augmenting capsulolabral repair strength in an anterior instability model with subcritical bone loss. These data represent biomechanical justification for the utilization of this relatively novel technique.